Concept of International Criminology Branching in Domestic Science of International Law - Широкова-Мурараш, О. Г. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article there is investigated a question on development of new scientifically reasonable approachesin research of terrorism as an international crime, in particular, creation of international criminology branchingconcept in domestic science of international law.